Influência do treinamento físico aeróbio no remodelamento cardíaco de ratos espontaneamente hipertensos tratados com Dexametasona - Souza, Francine Duchatsch Ribeiro de (Universidade Federal de São Carlos, 2019)
It has been shown that chronic treatment with dexamethasone (DEX) promotes cardiac remodeling and hypertension (H) in normotensive rats, however little is known about the effects of DEX in spontaneously hypertensive animals (SHR). In contrast, aerobic physical training (T) has been used as a non-pharmacological treatment in hypertension and one of its mechanisms is the improvement on cardiac remodeling. Therefore, the objective of the present study was to investigate the effects of DEX treatment and aerobic training on AP and cardiac remodeling process in SHR. For this purpose, 64 SHR (12 weeks) underwent treadmill T (60% of maximal capacity, 5 days / week, 1 h / day, for 75 days) or remained sedentary. During the last 15 days, the animals were treated with low dose of DEX (50 μg / kg body weight per day, s.c.) or saline. A group of 20 sedentary Wistar rats (W, 12 weeks) were used as control. After the experimental protocol, all rats were submitted to echocardiography, fasting blood glucose, carotid artery catheterization for AP and heart rate (HR) measurements and analysis of the autonomic nervous system. Subsequently, heart was removed for analysis of cardiac mass, capillary density, myocyte diameter and left ventricle (LV) collagen density. Chronic treatment with DEX did not exacerbate mean AP (MAP) of SHR. However, T was effective in reducing MAP of SHR (~ 20%). Treatment with low dose of DEX did not alter systolic function, but increased LV diastolic diameter (LVDD / BW) and improved diastolic function, since it reduced the isovolumetric relaxation time (IVRT), increased capillary density (+ 19%), and reduced % of collagen in the LV (-22%), regardless of myocyte size. On the other hand, T in the SHR treated with DEX promoted increase in heart weight (11%), which suggests a beneficial mass increase, which was independent of myocyte size, increased posterior wall shortening velocity (PWSV), which also suggests an improvement in systolic function, as well as increased LVDD / BW and IVRT, as well as reduced % of collagen (-28%), indicating an improvement in diastolic function. In summary, the results of the present study indicate, for the first time, that chronic treatment with low dose of DEX does not exacerbate hemodynamic and autonomic variables in SHR, but improves LV diastolic function, increases angiogenesis and reduces % of collagen. Together with DEX treatment, T determined a significant reduction on AP and promoted cardiac remodeling that contributed to a significant improvement of LV systolic and diastolic function in SHR. These results may suggest that administration of DEX at low doses and at the time used in this study can be administered to the hypertensive population without major concerns.
Influence of aerobic physical training in heart remodeling on dexamethasone-treated spontaneously hypertensive rats
Keywords: Glicocorticoides; Remodelamento Cardíaco; Exercício Físico; Hipertensão Arterial; Glucocorticoids; Cardiac Remodeling; Physical Exercise; Hypertension; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS